Dynamic immune and exosome transcriptomic responses in patients undergoing psychostimulant methamphetamine withdrawal - Wu, Hongjin; Zhang, Zunyue; Ma, Yuru; Chen, Fengrong; Xiong, Pu; Xie, Zhenrong; Ding, Guo; Yu, Juehua; Wang, Kunhua (Frontiers in Cellular Neuroscience, 2022)
Methamphetamine (METH) addiction and withdrawal cause serious harm to both the immune system and nervous system. However, the pathogenesis remains largely unknown. Herein, we investigated the peripheral cytokines and exosomal transcriptome regulatory networks in the patients with METH use disorders (MUDs) undergoing withdrawal. Twenty-seven cytokines were simultaneously assessed in 51 subjects, including 22 at the acute withdrawal (AW) stage and 29 at the protracted withdrawal (PW) stage, and 31 age and gender-matched healthy controls (HCs). Compared to the HCs, significantly decreased levels of interleukin (IL)-1β, IL-9, IL-15, Basic FGF, and MIP1a, increased levels of IL-1rα, IL-6, Eotaxin IP-10, VEGF, and RANTES were identified in AW. These disturbances were mostly or partly restored to the baseline in PW. However, the cytokines IL-6, IL-7, and IL-12p70 were consistently increased even after one year of withdrawal. Besides, a significant decrease in CD3+T and CD4+T cell numbers was observed in AW, and the diminishment was restored to baseline in PW. Comparatively, there were no statistically significant changes in CD8+T, NK, and B cells. Furthermore, the exosomal mRNAs and long non-coding RNAs (lncRNA) were profiled, and the lncRNA-miRNA-mRNA networks were constructed and associated with METH AW and PW stages. Notably, the chemokine signaling was remarkably upregulated during AW. By contrast, the differentially expressed mRNAs/lincRNAs were significantly enriched in neurodegeneration-related diseases. Taken together, a group of METH withdrawal-related cytokines and exosomal mRNA/lncRNA regulatory networks were obtained, which provides a useful experimental and theoretical basis for further understanding of the pathogenesis of the withdrawal symptoms in MUDs.